Differential Targeting of Hsp70 Heat Shock Proteins HSPA6 and HSPA1A with Components of a Protein Disaggregation/Refolding Machine in Differentiated Human Neuronal Cells following Thermal Stress - Deane, Catherine A. S.; Brown, Ian R. (Frontiers in Neuroscience, 2017)
Heat shock proteins (Hsps) co-operate in multi-protein machines that counter protein misfolding and aggregation and involve DNAJ (Hsp40), HSPA (Hsp70) and HSPH (Hsp105α). The HSPA family is a multigene family composed of inducible and constitutively expressed members. Inducible HSPA6 (Hsp70B`) is found in the human genome but not in the genomes of mouse and rat. To advance knowledge of this little studied HSPA member, the targeting of HSPA6 to stress-sensitive neuronal sites with components of a disaggregation/refolding machine was investigated following thermal stress. HSPA6 targeted the periphery of nuclear speckles (perispeckles) that have been characterized as sites of transcription. However, HSPA6 did not co-localize at perispeckles with DNAJB1 (Hsp40-1) or HSPH1 (Hsp105α). At 3 h after heat shock, HSPA6 co-localized with these members of the disaggregation/refolding machine at the granular component (GC) of the nucleolus. Inducible HSPA1A (Hsp70-1) and constitutively expressed HSPA8 (Hsc70) co-localized at nuclear speckles with components of the machine immediately after heat shock, and at the GC layer of the nucleolus at 1 h with DNAJA1 and BAG-1. These results suggest that HSPA6 exhibits targeting features that are not apparent for HSPA1A and HSPA8.